P11 Induction of immunomodulatory cell death by synthetic RNA mimetics. Issue 5 (May 2015) - Klein, J.; Wild, C.A.; Lang, S.; Brandau, S.
Abstract : Background: Immune cells detect viral and bacterial DNA/RNA via specific so-called pattern recognition receptors (PRRs). Synthetic RNA and DNA mimetics stimulate defined immune cell subsets and are currently tested as novel immunotherapeutic agents against cancer with, however, varying clinical efficacy. Recent data showed the expression of RNA-recognizing receptors also on tumor cells. In this study we exposed human head and neck squamous cell carcinoma (HNSCC) cells to poly(I:C) and imiquimod, two commercially available immunotherapeutic RNA mimetics, and investigated immunological events associated with the induction of tumor cell death by these compounds. Methods: A HNSCC cell line was exposed to poly(I:C) and imiquimod, which were delivered via culture medium or into the cytosol via electroporation. Cell death and cell biological consequences thereof were analyzed in vitro . For in vivo analyses a human HNSCC xenograft model was used. Results: Poly(I:C) induced cell death only if delivered into the cytosol. Interestingly, injection of poly(I:C) into the tumor reduced tumor growth and induced tumor cell apoptosis in tumor bearing mice, whereas imiquimod did not affect tumor size. Cell death induced by poly(I:C) resulted in cytokine release (interleukin-6, type I interferon and CXCL-10) and activation of monocytes in vitro . Monocytes activated by the supernatant of cancer cells previously exposed to poly(I:C) recruited significantly more Th1 cells than monocytes exposed to control supernatants. If delivered exogenously, Imiquimod also induced tumor cell death and release of interleukin-6, but cell death was not associated with release of Th1 cytokines, interferons, monocyte activation and Th1 recruitment. Conclusion: Our data demonstrate the induction of immunostimulatory HNSCC cell death by intracellular delivery of poly(I:C). Interestingly, imiquimod also induced cancer cell death, but failed to promote additional immunostimulatory mechanisms. These findings have implications for the use of RNA mimetics in cancer immunotherapy and suggest the local delivery of RNA compounds. In addition to the well-known activation of immune cells, local delivery of RNA mimetics to the malignant tissue will induce additional tumor cell death associated with compound-specific promotion of local cellular immunity.